Fabrication of silver nanoparticles by a diethylene triamine-hyaluronic acid derivative and use as antibacterial coating. (1st November 2022) - Martorana, Annalisa; Pitarresi, Giovanna; Palumbo, Fabio Salvatore; Catania, Valentina; Schillaci, Domenico; Mauro, Nicolò; Fiorica, Calogero; Giammona, Gaetano
Abstract: In this work a synthetic protocol for the functionalization of hyaluronic acid with diethylenetriamine (DETA) was standardized. HA-DETA derivatives were characterized by NMR and proton carbon correlation analysis HSQC and HMBC to confirm chemical structure. A selected derivative was used to set up a green fabrication procedure for HA-DETA capped silver nanoparticles with the aim to achieve a polymeric based coating with potential application in the treatment of medical devices associated infections. Data from UV–visible spectroscopy, electron scanning and transmission microscope (STEM), photoelectric spectroscopy (XPS) and rheological characterization were combined to characterize the HA-DETA/Ag nanocomposites. HA-DETA stabilized Ag nanoparticles (10–30 nm) were obtained through an UV accelerated production. The viability of MC3T3-E1 was analyzed with the aim of designing a cytocompatible antimicrobial coating. Antibacterial and antibiofilm activity of HA-DETA/Ag nanocomposites have been tested in vitro against Staphylococcus aureus and Pseudomonas aeruginosa both in culture plates than on titanium specimens. Graphical abstract: Unlabelled Image